ANALYSIS OF BOLT SUPPLIER SELECTION USING AHP-TOPSIS AND FUZZY-AHP METHOD COMPARISON (PT STECHOQ ROBOTIKA INDONESIA) - Dzikri Rivaldi; Farida Pulansari; Ardi Puspa Kartika (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2023)
Nowadays, problems in the industry are increasingly dynamic, including the problem of sustainable supplier selection. Suppliers will significantly affect the stability of the supply chain, especially issues of accuracy, quality, and delivery time. PT Stechoq Robotika Indonesia is an R&D and manufacturing company that produces appropriate technology with bolt components supplied by seven suppliers. Cases of late deliveries that reach four working days have disrupted the smooth running of production, so it is necessary to review current suppliers with objective methods. This study evaluates bolt suppliers by comparing AHP-TOPSIS and FAHP methods according to specified criteria (price, quality, delivery time, accuracy, service). Both ways produce the same highest-value bolt supplier, Supplier #7, and there is a slight difference for the second and third-order suppliers, namely Supplier #1 or Supplier #3. The study results are used as recommendations in determining the main suppliers, supporting suppliers, and replacement or re-evaluation for the three suppliers with the lowest rank (Supplier #6, Supplier #5, and Supplier #4).